Restricted versus liberal intraoperative benzodiazepine use in cardiac anaesthesia for reducing delirium (B-Free Pilot): a pilot, multicentre, randomised, cluster crossover trial. (July 2020) - Spence, Jessica; Belley-Côté, Emilie; Jacobsohn, Eric; Lee, Shun Fu; Whitlock, Richard; Bangdiwala, Shrikant; Syed, Summer; Sarkaria, Anisha; MacIsaac, Sarah; Lengyel, Alexandra; Long, Steven; Um, Kevin; et al.
Abstract: Background: Delirium is common after cardiac surgery and is associated with adverse outcomes. Perioperative benzodiazepine use is associated with delirium and is common during cardiac surgery, which may increase the risk of postoperative delirium. We undertook a pilot study to inform the feasibility of a large randomised cluster crossover trial examining whether an institutional policy of restricted benzodiazepine administration during cardiac surgery (compared with liberal administration) would reduce delirium. Methods: We conducted a two-centre, pilot, randomised cluster crossover trial with four 4 week crossover periods. Each centre was randomised to a policy of restricted or liberal use, and then alternated between the two policies during the remaining three periods. Our feasibility outcomes were adherence to each policy (goal ≥80%) and outcome assessment (one delirium assessment per day in the ICU in ≥90% of participants). We also evaluated the incidence of intraoperative awareness in one site using serial Brice questionnaires. Results: Of 800 patients undergoing cardiac surgery during the trial period, 127/800 (15.9%) had delirium. Of these, 355/389 (91.3%) received benzodiazepines during the liberal benzodiazepine periods and 363/411 (88.3%) did not receive benzodiazepines during the restricted benzodiazepine periods. Amongst the 800 patients, 740 (92.5%) had ≥1 postoperative delirium assessment per day in the ICU. Of 521 patients screened for intraoperative awareness, one patient (0.2%), managed during the restricted benzodiazepine period (but who received benzodiazepine), experienced intraoperative awareness. Conclusions: This pilot study demonstrates the feasibility of a large, multicentre, randomised, cluster crossover trial examining whether an institutional policy of restricted vs liberal benzodiazepine use during cardiac surgery will reduce postoperative delirium. Clinical trial registration: NCT03053869.